PO113 Natalizumab treatment for ms: uk and global results from top. (1st December 2017) - Nicholas, Richard; Bretagne, Adrien; Chen, Yi; Syed Farooq, Syed Feisal; Ridley, Dan
Abstract : Introduction: The Tysabri ® Observational Program (TOP) is a 10 year, ongoing, global open-label study enrolling natalizumab-treated relapsing-remitting multiple sclerosis patients from clinical practice settings. Methods: We analysed pre- and on-natalizumab annualised relapse rates (ARRs) and the likelihood of 24 week confirmed Expanded Disability Status Scale (EDSS) worsening (score increase of ≥1.5 from 0.0, ≥1.0 from 1.0–5.5, or ≥0.5 from≥6.0) or improvement (score decrease of ≥1.0 from≥2.0). Results: As of 1 May 2016, TOP UK patients (n=134) and TOP rest of world (ROW) patients (n=5793) had received a median (range) of 50 (1–79) and 34 (1–113) doses, respectively. ARR decreased from 2.21 pre-natalizumab to 0.23 on-natalizumab (89.7%; p<0.0001) in the UK and from 1.99 to 0.22 (89.0%; p<0.0001) in ROW. In both cohorts, on-natalizumab ARRs decreased by 83.3%–86.4% in year 1 and remained ≤0.23 thereafter. At year 6, the cumulative risks of EDSS worsening were 23.9% (UK) and 24.1% (ROW), and the likelihoods of EDSS improvement were 33.9% (UK) and 32.3% (ROW). Conclusions: In the UK and ROW TOP cohorts, on-natalizumab ARRs and EDSS worsening rates remained low over ≥6 years. Support: Biogen. Disclosures: RN: grant, travel support from Biogen; AB, YC, SFSF, DR: employees of/hold stock/stock options in Biogen.